To the memory of Alexej Sitenko (Oleksij Sytenko) (Condensed Matter Physics, 2002)
Ukrainian and world science has suffered an irrelievable loss. A promine nt the- orist in physics, brilliant individual, true Ukrainian patriot Alexej Sitenk o (Oleksij Sytenko) passed away on February 11, 2002, one day before his 7 5th birthday.